Evaluation of the moisture resistance of rubberized asphalt using BBS/UTM bonding test, TSR and HWT test. (18th July 2022) - Lv, Quan; Lu, Jun; Tang, Xiong; Hu, Yanmin; Yan, Chuanqi
Highlights: A series of 16 types of rubberized asphalts is investigated. A novel UTM bonding method is proposed. A novel HWT analysis frame is proposed. The effect of post-compaction, loading and moisture in HWT is separated. Abstract: Extensive efforts have been devoted to recycling waste materials and reusing them in sustainable pavement. In this aspect, rubberized asphalt based on the waste truck tire is one of the most promising technologies. However, the moisture resistance of rubberized asphalt has always been a concern. This study attempts to investigate the moisture resistance of rubberized asphalt using two novel evaluation methods. From the asphalt binder aspect, a bonding energy indicator is derived from a novel universal tensile machine (UTM) bonding test to assess the direct bonding between the asphalt binder and the aggregate. As for mixture level, a new analysis frame is developed to separate the confounding effect in the Hamburg Wheel-Track (HWT) test, hence the influence of moisture can be exclusively quantified. For a comprehensive study, a series of 16 types of rubberized asphalts is investigated. Rubber content, rubber particle size, rubber particle type (sulfurized, desulfurized) and preparation temperature are considered. The results suggest that conventional bonding strength and TSR indicators cannot discriminate different types of rubberized asphalts and show a low correlation with each other (R 2  = 0.01). Bonding energy indicator puts more weight on the toughness of rubberized asphalt and thus shows a fair good correlation with HWT performance (R 2  = 0.48). The new HWT analysis frame further improves the correlation (R 2  = 0.55). This validates the feasibility of using these new methods to quantify the bonding performance of rubberized asphalt. By adjusting the rubber content, particle size and preparing temperature, the bonding performance of the rubberized asphalt can be notably improved.